The Mosquera and Arboleda families and the Bolivar project (1821-1830) - Pardo Arellano, Luis Ervin (Pontificia Universidad Javeriana, 2014)
This study intends to approach the relationship held by two of the most important families of the city of Popayan with General Simon Bolívar at the beginning of the 19th century. It particularly inquires about the interests those families had in their adherence to Bolivar’s Republic project; i.e., into a State with a strong executive power that was nearly solidified with a dictatorship.